Radial force cancellation of bearingless brushless direct current motor using integrated winding configuration - Ali A. Yousif; Ahmed M. Mohammed; Mohammed Moanes E. Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A bearingless brushless direct current (BLDC) motor incorporates the function of magnetic bearings into a BLDC motor, making it a new type of high-performance motor. In this paper, the main motor windings are used to generate the radial force cancellation by injecting the required dc current, “integrated winding configuration”. The bearingless BLDC motor, direct current (DC) cancellation system model is established with the aid of (ANSYS/MAXWELL) software. The simulation results confirm that the rotor radial force is approximately zero and results from a balanced distribution of the magnetic flux density. The proposed DC excitation system is suitable to realize the rotor radial force cancellation in the bearingless BLDC motor. The simulation results of the proposed configuration show the approach of integrating winding configuration at different active pole positions to find the more efficient suspension performance and reduce the suspensions system current.